The regulation of IGF-1 gene transcription and splicing during development and aging. - Anita eOberbauer (Frontiers in Endocrinology, 2013)
It is commonly known that the insulin-like growth factor-I gene contains six exons that can be differentially spliced to create multiple transcript variants. Further, there are two mutually exclusive leader exons each having multiple promoter sites that are variably used. The mature IGF-I protein derived from the multiplicity of transcripts does not differ suggesting a regulatory role for the various transcript isoforms. The variant forms possess different stabilities, binding partners, and activity indicating a pivotal role for the isoforms. Research has demonstrated differential expression of the IGF-I mRNA transcripts in response to steroids, growth hormone, and developmental cues. Many studies of different tissues have focused on assessing the presence, or putative action, of the transcript isoforms with little consideration of the transcriptional mechanisms that generate the variants or the translational use of the transcript isoforms. Control points for the latter include epigenetic regulation of splicing and promoter usage in response to development or injury, RNA binding proteins and miRNA effects on transcript stability, and preferential use of two leader exons by GH and other hormones. This review will detail the current knowledge of the mechanical, hormonal, and developmental stimuli regulating IGF1 promoter usage and splicing machinery used to create the variants.